On origin of rapid portion of luminance-voltage dependence of ZnS:Mn TFEL devices and its aging behavior - Vlasenko, N.A.; Denisova, Z.L.; Kononets, Ya.F.; Veligura, L.I.; Chumachkova, M.M.; Tsyrkunov, Yu.A.; Soininen, E.L.; Tornqvist, R.O.; Vasame, K.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Some peculiarities in the rapid portion of the voltage dependences of luminance and transferred charge as well as in its aging behavior in ZnS:Mn thin film electroluminescent devices made by different deposition techniques have been revealed. The devices with nearly the same Mn concentration (~1 at. %) were deposited by electron-beam evaporation and two atomic-layer epitaxy processes based on chlorine (ZnCl₂, MnCl₂) or organic (diethyl Zn and Mn(thd)₃ ) precursors. It has been studied interrelation between these peculiarities and the differences observed in the photodepolarization spectra of the devices, which give data about defects in the ZnS:Mn films and the energy of corresponding local states in them. The obtained results are discussed as to physical processes responsible for the rapid portion of the above voltage dependences and for the causes of its change after short-time accelerated aging.